2006 IEEE Aerospace Conference
DOI: 10.1109/aero.2006.1655756
|View full text |Cite
|
Sign up to set email alerts
|

Deployable Wood Wasp Drill for Planetary Subsurface Sampling

Abstract: 1,2 -Growing interest in planetary subsurface exploration has prompted an examination of advanced drilling technologies. One of the major limitations of sampling in low gravity environments (such as Mars, asteroids, etc) using conventional rotary drills is the need for high axial force, which suffers from big overhead mass, buckling problem, and power hungriness. Though drills using percussive motion may operate in low mass and power, the drilling rate is generally slow. Drawing inspiration from nature for a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…During penetration, the entire mechanism resembles the root of a plant, with the monolithic structure extending from the tip, using an everted, pressure-driven membrane to achieve this. Because F I G U R E 9 Bionic penetrator: (a) imitation earthworm penetrator: the structure of earthworms (Menciassi et al, 2004), (b) imitation earthworm penetrator (Isaka et al, 2019), (c) propulsion principle of earthworm penetrator (Isaka et al, 2019), (d) imitation plant root tip growth penetrator: growth penetration of plant root tip cells (Sadeghi et al, 2013), (e) imitation plant root tip growth penetrator (Naclerio et al, 2018), (f) additive plant imitation penetrator (Sadeghi et al, 2014), (g) imitation inchworm penetrator (Zhang et al, 2020), (h) imitation carpenter bee double reciprocating penetrator (Gao et al, 2006), (i) imitation razor penetrator (Winter et al, 2014), (j) mole penetrator (Lee et al, 2019), and (k) hornet penetrator (Feng, 2018).…”
Section: Bionic Penetratorsmentioning
confidence: 99%
See 1 more Smart Citation
“…During penetration, the entire mechanism resembles the root of a plant, with the monolithic structure extending from the tip, using an everted, pressure-driven membrane to achieve this. Because F I G U R E 9 Bionic penetrator: (a) imitation earthworm penetrator: the structure of earthworms (Menciassi et al, 2004), (b) imitation earthworm penetrator (Isaka et al, 2019), (c) propulsion principle of earthworm penetrator (Isaka et al, 2019), (d) imitation plant root tip growth penetrator: growth penetration of plant root tip cells (Sadeghi et al, 2013), (e) imitation plant root tip growth penetrator (Naclerio et al, 2018), (f) additive plant imitation penetrator (Sadeghi et al, 2014), (g) imitation inchworm penetrator (Zhang et al, 2020), (h) imitation carpenter bee double reciprocating penetrator (Gao et al, 2006), (i) imitation razor penetrator (Winter et al, 2014), (j) mole penetrator (Lee et al, 2019), and (k) hornet penetrator (Feng, 2018).…”
Section: Bionic Penetratorsmentioning
confidence: 99%
“…Whereas fish in the ocean propel themselves through the water by generating thrust through their tail fins, sandfish also bury themselves in the sand through undulating body movements. Based on this principle, researchers have developed a dual reciprocating penetrator, which can simulate the wave penetration form for drilling (Gao et al, 2006(Gao et al, , 2007Gouache, Gao, et al, 2011;Gouache, Patel, et al, 2011;Pitcher & Gao, 2015). This penetrator not only bionics the wave drilling process but also bionics the drilling process of the carpenter bee.…”
Section: Bionic Penetratorsmentioning
confidence: 99%
“…Several prototypes exist that have been tested intensively in a wide range of substrates ranging from fine regolith simulants to icy substrates as the one shown in Figure 5C. Sakes et al (2020) developed a wood wasp inspired micro-drill prototype for minimal invasive surgery capable of achieving a stroke velocity of 4-8.77 mm/s and a transportation rate of up to 5.82 mg/ s. Still, a wood-wasp inspired drills for aerospace applications have yet to be deployed and tested within the space environment (Gao et al, 2006;Gouache et al, 2010;Pitcher et al, 2020;Alkalla et al, 2021).…”
Section: Planetary Exploration and Activitiesmentioning
confidence: 99%
“…It is found that high-frequency dynamic impact can reduce the contact stress between the coring tube and lunar soil particles and drive the lunar soil particles on the surface of the coring tube to move toward the lunar surface. The use of coring tubes with an anisotropic frictional surface profile can further enhance the transport effect of lunar soil particles and thus improve the coring rate [34,35]. The coring tube has wedge-shaped "barbs" on the inner and outer surfaces so that the lunar soil particles near the outer wall of the coring tube are discharged from the lunar surface.…”
Section: Process Analysis Of Coringmentioning
confidence: 99%